Divergent diffusion: Understanding the interaction between institutions, firms, networks and knowledge in the international adoption of technology - Galang, Roberto Martin N (Archīum Ateneo, 2014)
Why do certain technologies diffuse globally while others spread only within certain areas of the world? I analyze the uneven process of international technology diffusion by focusing on how institutions moderate the impact of firm, network, and knowledge characteristics on the adoption of technology. The study shows that better economic institutions lower transformation costs; that similarities across social institutions minimize transmission costs; and that effective political institutions reduce transaction costs for technology diffusion. The impact of each institution-type on the diffusion process is based on the relative weight of the three different knowledge dimensions embedded in the technology. Complex technologies are most affected by economic institutions; tacit technologies are most dependent on social institutions; and systemic technologies are most influenced by political institutions.